Smart Home System Control Using GSM (International Journal of Engineering and Computer Science, 2018)
Home automation is becoming more and more popular day by day due to its numerous advantages. This can be achieved by local networking or by remote control.In existing system, the control of smart home is via Bluetooth and internet connectivity. There is only fire sensor in the smart home, if there is any problem due to that sensor there is indication through alarm like buzzer and there is an email alert to the user. Here the Bluetooth is used for short distance communication and internet is used for long distance communication.